Which role do education and training play in the digital transformation process? - Baum, Myriam [Verfasser]; Lukowski, Felix [Verfasser] (My University, 2019)
"The focus of the digitalisation debate is often centred on technological progress and its diffusion into company processes. Less attention is accorded to the endeavours undertaken by companies to impart required competen-cies. This article uses the BIBB Training Panel to investigate the correlation between company promotion of competencies and use of technology." (Author's abstract ; BIBB-Doku)
Welche Rolle spielt Bildung im digitalen Transformationsprozess?
Keywords: G 2.2 Informations- / Wissensgesellschaft; S 1.5.3 Betriebliche Weiterbildung; BIBB-Qualifizierungspanel; Informationstechnische Bildung; Betriebliche Weiterbildung; Fachkräftequalifizierung; Digitalisierung